Zoning Regulation as Land Use Control Instrument: Lesson Learned from United States of America and Singapore - Korlena Korlena; Achmad Djunaedi; Leksono Probosubanu; Nurhasan Ismail (Faculty of Engineering, Universitas Gadjah Mada, 2010)
One of local government authorities is the implementation of land use planning. Due to implementation land use planning, controlling is needed as effort for the implementation is appropriate with the planning. According to Spatial Planning Act No.26/2007, land use control instruments are zoning regulation, permit, incentive and disincentive, and sanction. In Indonesia, zoning regulation is new instrument and only a few of city that have made and uses zoning regulation as land use control instrument. Local government has to create zoning regulation and uses it to control land use in their area. Comparative study is needed to learn from other countries that use zoning regulation as land use control instrument successful.United State of America and Singapore are relevant as cases study because of their success in using of zoning regulation. This study used a descriptive approach with literature sources. The results show that: (1) there is similarity between United State of America (USA) and Singapore in success using zoning regulation as instrument of land use control; (2) There is different type of land use control system. Most of cities in USA, except Houston City, use regulatory system. Inthis system, decision for a land use application is only based on zoning regulation. While Singapore uses discretionary system, the owner’s right to develop is controlled, not only by a zoning regulation, but also by a planning authority’s discretion. Keywords: zoning regulation, land use control, regulatory system, discretionary system